Association of body mass index and osteoarthritis with healthcare expenditures and utilization. (13th January 2020) - Johnston, Stephen S.; Ammann, Eric; Scamuffa, Robin; Samuels, Jonathan; Stokes, Andrew; Fegelman, Elliott; Hsiao, Chia‐Wen
Summary: Objective: Osteoarthritis is highly prevalent and, on aggregate, is one of the largest contributors to US spending on hospital‐based health care. This study sought to examine body mass index (BMI)–related variation in the association of osteoarthritis with healthcare utilization and expenditures. Methods: This is a retrospective study using administrative insurance claims linked to electronic health records. Study patients were aged ≥ 18 years with ≥1 BMI measurement recorded in 2014, with the first ( index ) BMI ≥ 25 kg m −2 . Study outcomes and covariates were measured during a 1‐year evaluation period spanning 6 months before and after index. Multivariable regression analyses examined the association of BMI with osteoarthritis prevalence, and the combined associations of osteoarthritis and BMI with osteoarthritis‐related medication utilization, all‐cause hospitalization, and healthcare expenditures. Results: A total of 256 459 patients (median age = 56 y) met study eligibility criteria; 14.8% (38 050) had osteoarthritis. In multivariable analyses, the adjusted prevalence of osteoarthritis increased with increasing BMI (12.7% in patients who were overweight [25.0‐29.9 kg m −2 ] to 21.9% in patients with class III obesity [BMI ≥ 40 kg m −2 ], P < .001). Among patients with osteoarthritis, increasing BMI (from overweight to class III obesity) was associated with increased (all P < .01): utilization rates for analgesic medications (41.5‐53.5%); rates of all‐cause hospitalization (26.3%‐32.0%); and total healthcare expenditures (18 204‐23 372). Conclusion: The prevalence and economic burden of osteoarthritis grow with increasing BMI; primary prevention of weight‐related osteoarthritis and secondary weight management may help to alleviate this burden.